Impacts of agricultural commodity frontier expansion on smallholder livelihoods: An assessment through the lens of access to land and resources in the Argentine Chaco. (July 2022) - del Giorgio, Olivia; Robinson, Brian E.; le Polain de Waroux, Yann
Abstract: The global restructuring of productive systems in the last few decades has led to the rapid expansion of large-scale, industrial agriculture. This agricultural expansion has occurred by means of the acquisition and consolidation of vast tracts of land by agribusinesses, fundamentally changing the dynamics of land control. In order to secure access to resources, agribusinesses employ tactics of privatization and enclosure, which are supported by state-led processes of legalization and territorialization, as well as tactics of intimidation and violence. For smallholders faced with such pressures, maintaining access to land and resources is of critical importance. Here, we examine how changing access to land and resources influences what livelihood strategies smallholders are able to pursue in the Argentine Gran Chaco, a region that is experiencing high rates of deforestation for the expansion of large-scale soybean and cattle production. Our findings indicate that the ability of smallholders to engage in activities critical to their livelihoods has been impacted by changes in access brought about by the expansion of commodity frontiers in the Gran Chaco, leading to a restructuring of these activities. In particular, we found that cattle and goat herding were constrained by the spatial conditions and relational pressures associated with frontier expansion, possibly leading to a greater reliance on pig rearing, but that smallholders who deployed access mechanisms, such as working with lawyers to obtain land titles, were better able to maintain these activities. Our results demonstrate the value of adopting a disaggregated view on the different dimensions of smallholder access, and more generally highlight the need to assess smallholders' access to land and resources, rather than merely the availability of resources, in order to better understand the impacts of agricultural commodity frontier expansion and properly target policy to reduce smallholder vulnerability. Highlights: Access to land is critical for smallholder livelihoods. Agricultural commodity frontier expansion is paralleled by changes in land control. Changes in land control lead to loss of land access for smallholders. Livelihood impacts depend on land access mechanisms, pressures, and conditions. Disaggregating dimensions of access better reveal livelihood constraints.